Pelatihan Proses Pelaksanaan Perencanaan Pembelajaran Harian di PAUD Al-Amin - Sitorus, Ahmad Syukri; Pohan, Isra’ Mianda; Nasution, Adelia Hanjani; Rambe, Saima Nurputri; Putri, Fadhillah Salsabila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This activity aims to describe the understanding of PAUD teachers on lesson planning and improve the pedagogic and professional competence of PAUD teachers. With this activity the teacher must realize that making lesson plans is not just making but must really understand. And with this training, teachers can add insight or ability to design play activities in PAUD. The type of research used is qualitative research. The research was conducted at Al-Amin PAUD, Telaga Tujuh Village, Labuhan Deli. The research design is phenomenology. The data sources in this study were informants consisting of the committee and Al-Amin PAUD teachers. The implementation of this activity is carried out using the training method. And the data collection technique in this training is documentation. The results of the study show that in designing or making RPPH the teacher is quite enthusiastic and begins to understand the preparation of RPPH. By understanding the RPPH, the teacher displays a confident appearance and raises teaching skills. And teachers must really understand how the design process and designing learning plans are made attractive according to the characteristics and development of early childhood. Keywords: Training; Planning; Al-Amin.